Entre o Òrun e o Àiye : relação candomblé e política na região metropolitana da Grande Vitória - ES - Ribeiro, Iljorvanio Silva (2016)
The dissertation is concern on the Anthropology of the Afro-Brazilian populations, and focus on the processes of social interaction that led three priests of candomblé to contest municipal elections. Through a etnhographic point of view, it was described as a relation between the biographies, the different political and religious capitals and how this designation favored the visions of the political doing in the public space. Despite the common image of a secular State, there is a increase interest in promoting religious specificities in the public arena, and building a political party agenda is a growing subject of disputes.